Pengaruh Generalisasi Unit Lahan pada besarnya Erosi (Studi kasus di DAS Air Nelas, Propinsi Bengkulu) - Bambang Sulistyo (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
Effect of Land Unit Generalization on the ErosionLevel (Study Case in Air Nelas Watershed, Bengkulu Province)The research aims to identify the effect of land unit generalisasion on the erosion at the Air Nelas catchment area in Bengkulu Province. Land unit generalisation is one step to be done in arrangin RTL-RLKT (Rencana Teknik Lapangan-Rehabilitasi Lahan dan Konservasi Tanah; Field Planning for Soil Rehabilitation and Conservation) conducted by Balai Pengelola DAS (formerly Balai RLKT).Method applied by conducting digital analysis using GIS Program to calculate erosion of the catchment area with USLE (Universal Soil Loss Equation) formula. Comparison analysis was done between the result of erosion before and after land unit generalisation. Land unit generalisation is a process to eliminate land unit having area 1 cm2 on map or 25 hectares on the field at the scale of 1:50.000. The instruction to run generalisation in ArchInfo GIS program is ELIMINATE. Land unit generalisation is done to simplify map analysis manual by avoiding land unit which is very small in the area.The research result showed that for the whole Air Nelas catchment area the erosion rate was 601,279.49 ton/ha/year before generalisation and 267,907.54 ton/ha/year after generalisation, indicating that there was a 33,371.95 ton/ha/year difference or 55.44% as the effect of land unit generalisation process. When the observation was mainly at the area of rehabilitation and conservation, there were categorical changes of the erosion i.e. from Moderate to Heavy or Very Heavy and vice versa. The change was varying between 148,244.82 ton/ha/year (Moderate to Very Heavy) and 79,470.62 ton/ha/year (Very Heavy to Moderate). Overall, the erosion was increaasing aas 65,335.90 ton/ha/year (11,01%) for the whole category in area where rehabilitatin and conservation have to be conducted. Those changes would affect the plan which determine recommendations to be taken in rehabilitation and conservation of catchment areas, as well as change in the project location and budget.